Crossing the Border between Reality and Fiction in Martin McDonagh’s The Pillowman (Philologia, 2021)
Martin McDonagh is a contemporary British writer with Irish parents and his play The Pillowman unrolls in an unidentifiable totalitarian setting, tackling problems related to author-work-reader relationship. The paper focuses on reality-fiction interaction at the level of the process of creation and on the impact of the work of art on the readers. McDonagh’s play is a warning against the influence the audience may have on the writer and against the impulses a work of art raises in a reader, presenting the entire process as a cyclic movement having reality as a starting point and return to reality.
Keywords: reality; fiction; British contemporary drama; the process of creation; fiction transposed into reality; border-crossing